LEMBAGA MEDIASI PERBANKAN DALAM PENYELESAIAN SENGKETA - Denico Doly (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2012)
Banks ini Indonesia didn't miss from a problem betweem banks and costumers. Various problems faced by the banks ever in Indonesia. Completion of dispute can be passed through the court and outside court. Settlement of disputes outside the courts and more variety. One out of court dipute resolution is mediation. Mediation in the banking sector has been regulated in the regulation of the Banking Mediation. Establishment of banking mediation has also been mandated by the regulation. However, the implementation Banking Mediation Institute can not be realized. Therefore, in order to provide consumer protection, to the establishment of an institution that can provide the facility in providing dispute resolution, especially in banking activities.